2019
DOI: 10.1186/s12887-018-1380-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gestational age in the psychometric testing of the Bernese Pain Scale for Neonates

Abstract: BackgroundAssessing pain in neonates is challenging because full-term and preterm neonates of different gestational ages (GAs) have widely varied reactions to pain. We validated the Bernese Pain Scale for Neonates (BPSN) by testing its use among a large sample of neonates that represented all GAs.MethodsIn this prospective multisite validation study, we assessed 154 neonates between 24 2/7 and 41 4/7 weeks GA, based on the results of 1–5 capillary heel sticks in their first 14 days of life. From each heel stic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 69 publications
(103 reference statements)
1
19
0
2
Order By: Relevance
“…Very preterm neonates may show less change in heart rate because they are in a state of constant autonomic arousal caused by repeated painful and stressful procedures, which they often experience during their NICU stay (Gibbins, Stevens, McGrath, et al, 2008; Grunau, Oberlander, Whitfield, Fitzgerald, & Lee, 2001). These findings, as well as the results of our previous study (Schenk et al, 2019), indicate the importance of considering a neonate's GA or PMA in pain assessment. The more premature the neonate, the less pronounced is his or her pain response.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Very preterm neonates may show less change in heart rate because they are in a state of constant autonomic arousal caused by repeated painful and stressful procedures, which they often experience during their NICU stay (Gibbins, Stevens, McGrath, et al, 2008; Grunau, Oberlander, Whitfield, Fitzgerald, & Lee, 2001). These findings, as well as the results of our previous study (Schenk et al, 2019), indicate the importance of considering a neonate's GA or PMA in pain assessment. The more premature the neonate, the less pronounced is his or her pain response.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings supported the modified BPSN’s validity and demonstrated its reliability in a Swiss sample of 154 full‐term and preterm neonates with different GA. Furthermore, our findings showed that the younger the GA, the lower the cut‐off point should be that discriminates between no or low pain and moderate to severe pain (Schenk et al, 2019).…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, in nonverbal individuals, such as neonates, it is very difficult to distinguish between pain and other reasons that cause certain behavioral or physiologic responses, such as agitation or hunger (Hodgkinson et al, 1994). In fact, in neonatal infants, nonspecific physiologic and behavioral indicators of pain may occur during nonpainful stress experiences, making accurate pain assessment difficult (Hummel & van Dijk, 2006;Schenk et al, 2019).…”
Section: Discussionmentioning
confidence: 99%